2021
DOI: 10.1017/s1041610220000678
|View full text |Cite
|
Sign up to set email alerts
|

Mild behavioral impairment as a predictor of cognitive functioning in older adults

Abstract: Objective: To assess the influence of mild behavioral impairment (MBI) on the cognitive performance of older adults who are cognitively healthy or have mild cognitive impairment (MCI). Methods: Secondary data analysis of a sample (n = 497) of older adults from the Florida Alzheimer’s Disease Research Center who were either cognitively healthy (n = 285) or diagnosed with MCI (n = 212). Over half of the sample (n = 255) met the operationalized diagnostic criteria for MBI. Cognitive domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…Cognitive and behavioral pre-dementia risk axes. [10][11][12][13][14][15][16][17], as well as known dementia markers including amyloid-␤ [18], tau [19,20], neurofilament light [21], temporal lobe atrophy [22,23], frontal lobe atrophy [24], white matter atrophy [25], functional dysconnectivity [26,27], and AD genetic loci [28,29]. This body of evidence suggests that in some older adults, MBI may be a consequence of emerging dementia proteinopathies which manifest independently or in concert with cognitive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive and behavioral pre-dementia risk axes. [10][11][12][13][14][15][16][17], as well as known dementia markers including amyloid-␤ [18], tau [19,20], neurofilament light [21], temporal lobe atrophy [22,23], frontal lobe atrophy [24], white matter atrophy [25], functional dysconnectivity [26,27], and AD genetic loci [28,29]. This body of evidence suggests that in some older adults, MBI may be a consequence of emerging dementia proteinopathies which manifest independently or in concert with cognitive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In a 2 (MCI: presence or absence) × 2 (MBI: presence or absence) Multivariate Analysis of Co-Variance, Rouse et al (2020) showed that, regardless of cognitive status, MBI was associated with poorer executive function, attention and episodic memory; and that co-morbid presentation of MBI and mild cognitive impairment resulted in significantly poorer performance on tasks of episodic memory when compared to a mild cognitive impairment only cohort. The authors conclude that the current findings not only corroborate the notion of MBI as an at-risk state for cognitive decline (e.g.…”
mentioning
confidence: 96%
“…Having said that, the prevalence rates reported across all three studies (Mortby et al, 2018b, Rouse et al, 2020, Sheikh et al, 2018 need to be interpreted with caution, as they may in fact represent inflated prevalence rates. The reason for this is the discrepancy between the reference timeframes used by the assessment tools.…”
mentioning
confidence: 99%
See 2 more Smart Citations